2010
DOI: 10.1016/j.atmosenv.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of levoglucosan in aerosols over the western North Pacific and its assessment as a biomass-burning tracer

Abstract: Levoglucosan is considered as a useful molecular tracer of biomass-burning aerosols in the atmosphere.To characterize the seasonal variation of its concentrations over the Pacific Ocean and to assess its usefulness as a tracer after long-range transport, we investigated long-term variations of levoglucosan over Chichi-jima in Chichi-jima and the East Asian coastal region. Conversely, the measured concentrations of levoglucosan in the summer are significantly lower than the modeled one. This implies a degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 42 publications
(4 reference statements)
8
105
0
1
Order By: Relevance
“…Shiraiwa et al (2012) studied the reactions between levoglucosan and NO 3 radicals and showed levoglucosan can be stable for just one week during NO 3 aging. On regional scale, Mochida et al (2010) observed a significant decay of levoglucosan in summer after long range transport. Using the SPACCIM model, Hoffmann et al (2010) also concluded that the lifetime of levoglucosan is 12.7e33.1 h in summer and 72.8e83.2 h in winter due to the oxidation of levoglucosan by OH radicals in aqueous phases.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Shiraiwa et al (2012) studied the reactions between levoglucosan and NO 3 radicals and showed levoglucosan can be stable for just one week during NO 3 aging. On regional scale, Mochida et al (2010) observed a significant decay of levoglucosan in summer after long range transport. Using the SPACCIM model, Hoffmann et al (2010) also concluded that the lifetime of levoglucosan is 12.7e33.1 h in summer and 72.8e83.2 h in winter due to the oxidation of levoglucosan by OH radicals in aqueous phases.…”
Section: Introductionmentioning
confidence: 97%
“…Levoglucosan (1,6-Anhydro-b-Dglucopyranose) is a specific component of particles emitted through biomass burning, and has recently been widely used as a molecular tracer in source apportionment (Engling et al, 2006;Mochida et al, 2010;Simoneit and Elias, 2001). A basic assumption in source apportionment models is that the tracers are stable in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Levoglucosan was found to be one of the dominant compounds among the individually identified compounds with a concentration range of 37e148 ng m À3 at PKU versus 34e149 ng m À3 at Yufa, indicating a significant impact of biomass burning to the summertime aerosols in Beijing. The ratio of levoglucosan to OC (levoglucosan/OC) has been used to estimate the contribution from biomass burning to the aerosol OC (Puxbaum et al, 2007;Mochida et al, 2010). The levoglucosan/OC ratio was generally higher at Yufa than at PKU (Fig.…”
Section: Biomass Burningmentioning
confidence: 99%
“…Anhydrosugars, such as levoglucosan, mannosan, and galactosan, are well established molecular tracers for biomass burning emissions, as they are solely derived from the thermal decomposition of cellulose and hemicelluloses (Simoneit et al, 1999). Although recent laboratory studies have revealed that these tracers may be degraded in the presence of oxidants, such as OH radicals (Hennigan et al, 2010;Hoffmann et al, 2010), the anhydrosugars can be used at least as qualitative indicators of biomass burning influence, but also for quantitative estimates of biomass smoke contributions when transport distances are shorter (Mochida et al, 2010), as was the case with the haze episode in this study. Hennigan et al (2010) reported that approximately 30-75 % of levoglucosan would react within one day at typical atmospheric OH levels while Hoffmann et al (2010) estimated the half-life of levoglucosan to be 12.7-83.2 h (0.5-3.5 days) at 90 % relative humidity.…”
Section: Chemical Speciation Of Tspmentioning
confidence: 99%